Forecasting the Number of Visitors in a Unique Recreational Site- A Retrospective View - Mira G. Baron; Natalia Zaitsev (European Regional Science Association (ERSA), 2011)
We examine in the research forecasts prepared by us fifteen years ago. We examine the assumptions made as well as the results, comparing the forecasts to reality. We concentrate on the forecasts of number of visitors, which enables to examine economic impact, and is crucial in analyzing ecological carrying capacity. Our case study was a wetland that was drained in the '50s, resulting in severe environmental damages. In the '90s part of the area was re-flooded and a small lake was created. We forecasted the number of visitors, the expected revenues and benefits. The area is currently called Agmon Hula, located in the previous Hula marsh (North of Israel). The commodity planned was a site which offers safari, birds' sanctuary, horse riding, swimming in a pool, picnicking. We asked recreationists in adjacent national parks and nature reserves on their willingness to visit the planned park and their willingness to pay (WTP), using CVM methods. In reality, the site started operation in 2005 as a birds' sanctuary, due to its success in attracting birds. 500 million birds pass the area twice per year migrating to the south in the fall and returning north in the spring. Our forecast for 380 thousand visitors in the first year of operation did not materialize. We could have predicted a smaller number closer to the real number (220 thousand) if we would have considered the percentage that ranked birds' sanctuary as one of their two favorite activities. The prediction assumed an annual increase in the number of visitors of 2-6%, but actually, the increase in the first five years of operation is 8% annually. In the prediction, we disregarded tourists, but they were 7-17% of the visitors. Updating the prediction of number of visitors is easy, and is a crucial aspect in predicting carrying capacity.
Keywords: 330